ANALISIS KRITIS: KEPEMIMPINAN DAN KEBIJAKAN PENDIDIKAN ISLAM DI INDONESIA - M. Hanif Satria Budi; Abd. Aziz; Nur Efendi; Miftakhul Maesaroh; Subhan Fathu Alam; Luthfin Mahamida (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2025)
Islamic education plays a strategic role in shaping the character, morality, and intellectual development of the Indonesian nation while serving as an integral component of the national education system. However, the effectiveness of Islamic education implementation largely depends on the synergy between leadership and educational policies applied across institutional levels. This study aims to analyze leadership and Islamic education policies in Indonesia. The main issues examined include the analysis of Islamic education policies, the role of leaders in policy formulation, and the impact of these policies on the practice and management of Islamic education. This research employs a library research design with a descriptive qualitative approach, examining various academic literatures and recent studies from national sources. Data were analyzed using content analysis techniques through the stages of data reduction, thematic classification, theoretical interpretation, and deductive conclusion drawing. The results indicate that Islamic education policies in Indonesia focus on improving institutional quality through curriculum enhancement, teacher professionalism, modern governance, and leadership grounded in Islamic values. The integration of religious and general sciences is realized through policies such as the Merdeka Curriculum and Madrasah Reform Policy, which emphasize Islamic character formation. Furthermore, digitalization initiatives—such as EMIS, SIMPATIKA, and the Digital Madrasah program—have enhanced the efficiency and innovation of learning processes. Nevertheless, challenges remain, including managerial disparities and low levels of digital literacy. Therefore, future policies should strengthen transformational leadership, adaptive decentralization, and the integration of Islamic ethics within all educational institutions.